Lipid Metabolism Regulation Based on Nanotechnology for Enhancement of Tumor Immunity - Tu, Bin; Gao, Yanrong; Sun, Feifei; Shi, Mingjie; Huang, Yongzhuo (Frontiers in Pharmacology, 2022)
The hallmarks of cancer include dysregulated metabolism and immune evasion. As a basic way of metabolism, lipid metabolism is reprogrammed for the rapid energy and nutrient supply in the occurrence and development of tumors. Lipid metabolism alterations that occur in the tumor microenvironment (TME) affect the antitumor responses of immune cells and cause immune evasion. Therefore, targeting lipid metabolism in the TME for enhancing the antitumor effect of immune cells is a promising direction for cancer treatment. Cancer nanomedicine has great potential in regulating tumor metabolism and tumor immunity. This review summarizes nanotechnology-based antitumor immune enhancement through regulation of the lipid metabolism in the TME.